The history of the social sciences since 1945 - Backhouse, Roger; Fontaine, Philippe (Cambridge University Press, 2010)
"This compact volume covers the main developments in the social sciences since the Second World War. Chapters on economics, human geography, political science, psychology, social anthropology, and sociology will interest anyone wanting short, accessible histories of those disciplines, all written by experts in the relevant field; they will also make it easy for readers to make comparisons between disciplines. A final chapter proposes a blueprint for a history of the social sciences as a whole. Whereas most of the existing literature considers the social sciences in isolation from one other, this volume shows that they have much in common; for example, they have responded to common problems using overlapping methods, and cross-disciplinary activities have been widespread. The focus throughout the book is on societal pressures on knowledge production rather than just theoretical lineages. This book is noteworthy because it: Is the first book that puts together histories of the main social sciences since World War II, each written by a discipline specialist; Enables the readers to realize that what they see as specific to their own discipline is in fact common to several; Contains a chapter that proposes a blueprint for a history of the social sciences as a whole"--